2015
DOI: 10.1007/s00408-014-9683-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Very Preterm Infants with Severe Respiratory Distress Syndrome Receiving Mechanical Ventilation

Abstract: The prognosis of very preterm infants with severe RDS may be influenced by several prenatal and postnatal factors. HFOV although decreased the duration of mechanical ventilation, whether it will decrease the incidence of neurodevelopmental disability, needs to be explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Neonatal RDS refers to a condition with respiratory failure and progressive respiratory distress shortly after the birth of an infant due to the lack of pulmonary surfactant and end-expiratory alveolar collapse, and in which an initial symptom is respiratory acidosis. In case of deterioration, the condition develops into metabolic acidosis, greatly affecting the life quality and survival rate of the newborn ( 5 , 6 ). The main clinical manifestations include cyanosis, polypnea, respiratory moaning inspiratory three depressions sign, and air bronchogram and ground-glass changes on chest X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal RDS refers to a condition with respiratory failure and progressive respiratory distress shortly after the birth of an infant due to the lack of pulmonary surfactant and end-expiratory alveolar collapse, and in which an initial symptom is respiratory acidosis. In case of deterioration, the condition develops into metabolic acidosis, greatly affecting the life quality and survival rate of the newborn ( 5 , 6 ). The main clinical manifestations include cyanosis, polypnea, respiratory moaning inspiratory three depressions sign, and air bronchogram and ground-glass changes on chest X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support that RDS is a risk factor for the development of IVH [25, 36, 37, 120, 121]. RDS is associated with the fluctuation of cerebral blood flow [122124], low blood pressure [125], use of mechanical ventilation and hypoxia-ischemia [126], all of which increase the risk of IVH.…”
Section: Discussionmentioning
confidence: 99%
“…No studies reported prevalence of any (aggregate of any severity) NDI at ≥5 years follow-up; prevalence of moderate-severe NDI was 10%. 84 The prevalence of any CP was 6% between 12 and 18 months follow-up, 67 7%–17% at 18 months to 2 years follow-up, 68,69,74 6%–33% between 2 and 5 years follow-up, 79,81 and 0% at ≥5 years follow-up. 84…”
Section: Resultsmentioning
confidence: 97%
“…Twenty studies from outside North America and Europe reported findings for NDI (Table 3). 12,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] Sample size ranged from eight (infants with focal intestinal perforation) to 2883. 73,83 Most (17/20) studies were retrospective.…”
Section: Ndi By Geographic Locationmentioning
confidence: 99%